Biotechnology of lactic acid bacteria : novel applications - Mozzi, Fernanda; Raya, Raul R.; Vignolo, Graciela M. (Ames, Iowa : Wiley-Blackwell, 2010)
'The book encompasses a wide range of topics including both traditional and novel developing fields, and provides unparalleled, comprehensive information on new advances of genomics, proteomics, metabolism and biodiversity of LAB. Chapters contain state-of-the-art discussions of specific LAB applications such as their use as probiotics, live vaccines and starter cultures in old and new fermented products. The safety of these microorganisms and their interactions with diverse ecosystems natural biota are also covered as well as the new applications of well-known (bacteriocins) and novel (vitamins, low-calorie sugars, etc.) metabolites produced by LAB'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Lactic acid bacteria; Microbial biotechnology; Lactobacillus -- Genetics; Lactobacillus -- metabolism; Biotechnology